COVID-19 musculoskeletal involvement in children - Giraudo, Chiara; Fichera, Giulia; Pilati, Lucia; Cortinovis, Anna Laura; Cavallin, Celeste; Bertin, Sofia; Zuliani, Monica; Cecchin, Diego (Frontiers in Pediatrics, 2023)
Since the early phases of the COVID-19 pandemic, it has become clear that children are affected by mild respiratory symptoms rather than the critical pneumonia typical in adults. Nevertheless, it took longer to understand that pediatric patients with SARS-COV2 may develop a severe multi-system inflammatory response (aka MIS-C), which can include musculoskeletal symptoms, and/or arthritis and myositis independently from MIS-C. Diagnostic imaging significantly con-tributed to the assessment of pulmonary disease due to COVID-19 but it has been rarely applied to evaluate musculoskeletal involvement in children with or without previous rheumatic diseases. Despite the paucity of radiological literature, muscle edema at Magnetic Resonance (MR) as well as synovitis at ultrasound have been described. A further use of diagnostic imaging for children with articular and muscular symptoms due to COVID-19 is strongly encouraged.